Chemical and transcriptomic analyses of leaf trichomes from Cistus creticus subsp. creticus reveal the biosynthetic pathways of certain labdane-type diterpenoids and their acetylated forms - Papanikolaou, Antigoni S (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.